Study protocol: the OxWell school survey investigating social, emotional and behavioural factors associated with mental health and well-being. Issue 12 (8th December 2021) - Mansfield, Karen Laura; Puntis, Stephen; Soneson, Emma; Cipriani, Andrea; Geulayov, Galit; Fazel, Mina
Abstract : Introduction: Improving our understanding of the broad range of social, emotional and behavioural factors that contribute to mental health outcomes in adolescents will be greatly enhanced with diverse, representative population samples. We present a protocol for a repeated self-report survey assessing risk and protective factors for mental health and well-being in school pupils aged 8–18 years with different socioeconomic backgrounds in England. The survey will provide a comprehensive picture of mental health and associated risks at the community level to inform the development of primary and secondary prevention and treatment strategies in schools. Methods and analysis: This protocol is for a large-scale online repeated self-report survey, representative of children and adolescents aged 8–18 years attending schools or further education colleges in participating counties in England. The survey consists of around 300 questions, including validated measures of mental health and well-being, risk and protective factors, and care-seeking behaviour and preferences. Additional questions each year vary to address current events and novel hypotheses, developed by the research team, collaborators and stakeholders. Primary analyses will investigate current and changing risk and protective factors, care-seeking behaviour and attitudes to allowing linkage of their sensitive data to other databases for research, and will compare measures of mental health to measures of well-being. Ethics and dissemination: The study was approved by the University of Oxford Research Ethics Committee (Reference: R62366). Tailored data summaries will be provided to participating schools and stakeholders within 3 months of data collection. The main findings will be presented at scientific meetings, published in peer-reviewed journals and shared via digital and social media channels. At the end of the study, other researchers will be able to apply for access to anonymous data extracts.